Probiotics and Prebiotics in Foodborne Illness: Mechanisms, Applications, and Future Directions - Louise Iara Gomes de Oliveira; Ana Rita Ribeiro de Araujo; Tatiana Colombo Pimentel; Vittorio Capozzi; Taliana Kenia Alves Bezerra; Marciane Magnani (Journal of Food Protection)
Foodborne diseases (FBDs) represent a global public health concern, with millions of reported annual cases resulting in significant outbreaks, hospitalizations, and deaths. In this context, probiotics and prebiotics emerge among the promising alternatives to antibiotics. This mini-review aims to analyze the available evidence, mechanisms, and perspectives on the possible role of probiotics and prebiotics in preventing or treating FBDs. Probiotics have demonstrated effectiveness against various pathogens by producing antimicrobial substances such as fatty acids, organic acids, volatile compounds, and bacteriocins, resulting in immune system regulation, reducing the viable number of these microorganisms, and eliminating or neutralizing their toxins. Furthermore, they may offer health benefits through the positive modulation of the gut microbiota, strengthening immunity, and reducing pathogen colonization. Prebiotics, in turn, act as substrates promoting the growth of probiotics and increasing the production of desired metabolites, such as short-chain fatty acids (SCFAs). SCFAs support probiotics in competing with pathogens, particularly for adhesion sites on intestinal cells. Prebiotics can also have direct antimicrobial action, controlling pathogen adhesion and modulating the immune system by stimulating cytokine production and improving intestinal barrier integrity. Although previous reviews have discussed the general benefits of probiotics and prebiotics, this mini-review offers a more in-depth analysis of their beneficial effects against FBDs. It also explores the isolated and combined potential of probiotics and prebiotics as therapeutic alternatives and adjuvants to classical antibiotic therapies in preventing and controlling foodborne diseases, pointing out the mechanisms that could help to improve global public health.